About Problems and Prospects of Humanities and Humanitarian Education in Russia - O. V. Vorobieva (Высшее образование в России)
The article presents reflections on the problems and prospects of humanities and humanitarian education in Russia, taking into account the basic program documents of the Russian state in the field of science and education. The author believes that in these documents the so-called social and humanitarian aspects characterizing functioning of science and innovations are insufficiently thought out. Meanwhile, these aspects reveal a powerful conglomerate of problems and opportunities – from the use of social and cultural knowledge as one of the sources of creativity and innovation, to the the implementation of forecasts and foresight, expert perception of development scenarios and managerial decisions, identifying risks and consequences in the process of increasing influence of science on nature, society and man, formation of value orientations and educational prospects. It is noted that in this situation it is very important to move away from a predominantly technocratic and economic understanding of the priorities and results of the scientific and technological development of Russia for a historical perspective, to avoid reducing information about the progress of a person, society, and the state to technological and economic criteria; to recognize a special status of Humanities, social sciences, and education as the most important resource confronting the technologically accelerated destruction of nature and society, to view them as a factor of cognition, dialogue and management.